IMMUNOTOXICITY OF LEAD AND ITS COMPOUNDS - Данилів, С. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Lead is one of the most toxic and dangerous to living organisms chemical element, the monitoring of which is necessarily. It is found that salts of this metal have expressed toxic action on cell membrane. Lead ions causes serious deformation of the body on the early stages of embryonic development and in adults organisms lead also causes degenerative and necrobiotic changes in gills and skin. Accumulation of lead in the body depends on gender, period, and the size of individuals. It is known that most metals accumulate in the smallest size organisms. Effect of lead ions depends on way of entering in the body: the intraperitoneal entering causes the increase of the spleen size, while adding it to drinking water causes the growth of the kidney. As in chronic poisoning, and under acute toxicant action inhibits the activity of the immune system. In particular, the presence of lead ions in environment leads to a decrease number of T- and B-lymphocytes and natural killers, an increase of neutrophils and reduce the number of monocytes, basophils and lymphocytes.